Communicating affirmative action in three South African organisations - Anné Leonard; Anské Grobler (Communicare)
Problems associated with the management of communication (in the broadest sense of the word) are a recurring theme in both Corporate Communication Management and Human Resource Management literature and in research on the implementation of affirmative action1 as part of the Employment Equity Act2 in the South African context. Therefore, the following research question was formulated: “How do South African organisations manage communication about affirmative action (against the backdrop of employment equity3)?”. This article provides an overview of some dimensions of an exploratory qualitative study that investigated this research question. The ever-increasing strategic importance of organisational performance regarding the EEA highlights the need for research in this area. This study is one of only a few empirical studies in the field of Corporate Communication with the emphasis on topics related to the management of communication in this specific transformational context. Since this study focused on aspects that had not been researched previously (or verified empirically), an exploratory approach had to be followed, with the purpose of gauging possible current trends related to the management of communication about AA in a selection of South African organisations. A case study comparison of three organisations yielded the following results on four sub-questions derived from the overarching research question. The organisations researched (1) comply with their legal duty to inform and consult with stakeholders about the process of EE as stipulated in the Code of Good Practice for the EEA (Department of Labour, 1999); (2) the management of EE is viewed as a transformational change process, as opposed to a once-off incident; (3) the